Evaluation of Propanediol and Cobalamin Metabolism in the Intestinal Colonization and Systemic Invasion of Salmonella Enteritidis in Laying Hens - Paiva, J. B.; Denadai, J. [UNESP]; Almeida, A. M. [UNESP]; Barrow, P. A.; Barbosa, F. O. [UNESP]; Alves, L. B.R. [UNESP]; Saraiva, M. M.S. [UNESP]; Oliveira, C. J.B.; Berchieri Júnior, A. [UNESP]; Freitas Neto, O. C. (FapUNIFESP (SciELO), 2020)
Experiments were performed in accordance with the ethical guidelines for the use of animals in research and approved by Ethics Committee on the Use of Animals of São Paulo State University – FCAV (Approval number: 023482/11).
Keywords: B12-dependent route; energy source; gut colonization; invasion; paratyphoid infection